Prediction of Bronchopulmonary Dysplasia in Preterm Infants Using Postnatal Risk Factors - Ding, Li; Wang, Huawei; Geng, Haifeng; Cui, Ningxun; Huang, Fengxia; Zhu, Xueping; Zhu, Xiaoli (Frontiers in Pediatrics, 2020)
Objective: To identify postnatal risk factors for bronchopulmonary dysplasia (BPD) development in preterm infants with gestational age ≤32 weeks. Methods: Seventy-two preterm infants(30 with BPD and 42 non-BPD controls) admitted in the neonatal intensive care unit (NICU) of the Children's Hospital of Soochow University during 2017 were enrolled in this prospective longitudinal study. Perinatal clinical data, a neonatal critical illness score (NCIS), different soluble B7-H3(sB7-H3), and interleukin-18 (IL-18) levels by days after birth were collected. An early predictive model for BPD development was established based on clinical data using multiple logistic regression analysis. And the sensitivity and specificity of the model were assesed by ROC curve. Results: Electrolyte disturbances, hemodynamically significant patent ductus arteriosus (hs-PDA), and the age that infants achieved 120 kcal/kg.d via enteral feeding ≥40 days after birth were found to be associated with the BPD pathogenesis. Serum sB7-H3, IL-18, and NCIS were significantly higher in the BPD group compared to the non-BPD group (p < 0.05). BPD group had significantly lower enteral fluid and caloric intake compared to the non-BPD group at 1, 7, 14, and 28 days after birth. The risk factors were analyzed by multiple logistic regression and a predictive model of a combination of sB7-H3 (day 7), IL-18 (day 14), NCIS, and clinical risk factors was evaluated via ROC curve with an area under the curve (AUC) of 0.960 having sensitivity of 86.7% and a specificity of 97.6%, respectively. Conclusion: The causes of BPD are multifactorial postnatal risk factors. And the combination of sB7-H3 (day 7), IL-18 (day 14), NCIS, and clinical risk factors (electrolyte disturbances, hs-PDA, and the age that infants achieved 120 kcal/kg.d via enteral feeding ≥40 days after birth) might be served as an optimal predictive model for the occurrence of BPD.